2017
DOI: 10.5194/bg-14-4243-2017
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties impacting denitrifier community size, structure, and activity in New Zealand dairy-grazed pasture

Abstract: Abstract. Denitrification is an anaerobic respiration process that is the primary contributor of the nitrous oxide (N 2 O) produced from grassland soils. Our objective was to gain insight into the relationships between denitrifier community size, structure, and activity for a range of pasture soils. We collected 10 dairy pasture soils with contrasting soil textures, drainage classes, management strategies (effluent irrigation or non-irrigation), and geographic locations in New Zealand, and measured their physi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Rangwala & Miller (2012) indicated that soil phosphorus limits plant productivity and indirectly affects soil microbial communities. Jha et al (2017) found that nosZ community structure had the strongest correlation with soil moisture content and available phosphorus. Those results were in agreement with our findings showing the relationship between nosZ- denitrifiers and soil properties.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Rangwala & Miller (2012) indicated that soil phosphorus limits plant productivity and indirectly affects soil microbial communities. Jha et al (2017) found that nosZ community structure had the strongest correlation with soil moisture content and available phosphorus. Those results were in agreement with our findings showing the relationship between nosZ- denitrifiers and soil properties.…”
Section: Discussionmentioning
confidence: 95%
“…Those results were in agreement with our findings showing the relationship between nosZ- denitrifiers and soil properties. While we focused specifically on nosZ abundance, previous studies have indicated that nirS and nirK communities are also strongly structured along gradients of soil water and phosphorus contents (Jha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that organic carbon is the limiting factor in microbial processes and activities in the early successional stages without vegetation cover, and carbon accumulation affects the availability of soil nitrogen (Wardle et al, 2004), in this sense, soil organic carbon and nitrogen levels in retreating glaciers can become the main driving factor in shaping the composition of nitrogen-related microbial communities, and soil pH is the most important factor impacting denitrification processes (Zeng et al, 2016;Čuhel et al, 2011 ;Kim et al, 2015). Jha et al (2017) have pointed out that the nosZ gene community structure had the strongest correlation with soil moisture content and available phosphorus. In a similar study, Tang et al (2016) showed that phosphorus had a strong influence on the abundance of nitrogencycling microorganisms in forest plantations, with a strong positive correlation between soil available phosphorus and nitrogen cycling-related microbial functional gene abundance.…”
Section: Relationships Between Nosz Denitrifying Bacterial Communitiementioning
confidence: 99%
“…More recent studies have used quantitative polymerase chain reaction (qPCR) to measure the abundance of key functional genes involved in N cycling (28), including amoA (nitrification) (31,32), narG (nitrate reduction) (33), nirK and nirS (nitrite reduction) (34), norB (NO reduction) (35), nosZ (N2O reduction) (36), and nifH (N2 fixation) (37). A growing body of evidence supports functional gene abundance as a useful index for predicting biogeochemical rates, particularly when applied to N process rates (33,(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%